2016
DOI: 10.22226/2410-3535-2016-4-355-359
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of trip effect in metastable steel by electrical current

Abstract: The present work deals with the problem of a possible application of current in deformation processes. A literature survey has shown an existence of publications on the electroplastic effect in single-phase materials without phase transformations and the lack of works on a study of the current impact on the deformation behavior of materials undergoing a phase transformation. Therefore, the influence of current regimes (density and impulse duration) and current mode (direct, pulse or multiple-pulse) on the defo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
(9 reference statements)
0
2
0
1
Order By: Relevance
“…In Fig. 3 the engineering stress-strain curves in the temperature range of 20 -200°C are presented (for completeness, curve 5 is reproduced from our earlier publication [13]). At a test temperature of 20°C (curve 1), beyond the yield point, as in a previous report, weak deformation hardening is observed [12].…”
Section: Resultsmentioning
confidence: 99%
“…In Fig. 3 the engineering stress-strain curves in the temperature range of 20 -200°C are presented (for completeness, curve 5 is reproduced from our earlier publication [13]). At a test temperature of 20°C (curve 1), beyond the yield point, as in a previous report, weak deformation hardening is observed [12].…”
Section: Resultsmentioning
confidence: 99%
“…Однако в стали 316L было установлено, что ЭПЭ при растяжении приводит к охрупчиванию за счет двойникования в структуре [16]. Оказалось, что воздействие тока может стимулировать или подавлять фазовые превращения [17]. Этот аспект наиболее интересен в приложении к ТРИП сталям, в которых прямое мартенситное превращение аустенит -мартенсит индуцируется пластической деформацией.…”
Section: Introductionunclassified
“…Qin et al [15] studied the role of different tilt GBs on MT in NiTi alloy during thermal cycling using MD method and concluded that some GBs retarded while the others promoted the martensite formation. There is also no general opinion about the effect of twin boundaries on MT [16,17] that can be responsible for the transformation induced plasticity effect [18].…”
Section: Introductionmentioning
confidence: 99%